WOMEN'S ENTREPRENEURSHIP IN SUPPORTING HALAL TOURISM IN LHOKSEUMAWE CITY - Bachri, Naufal; Wardhiah, Wardhiah; Roni, Muhammad; Muhammad Nur, Mukhlish (CV. Radja Publika, 2022)
This study aims to determine the entrepreneurial potential of Acehnese women in supporting halal tourism in Lhokseumawe City, to determine the obstacles and success factors of women in entrepreneurship, to know policies for empowering women in entrepreneurship, and to formulate a model for developing Acehnese women's entrepreneurship. This study uses a qualitative method with dialectical analysis. Data collection techniques are observation, in-depth interviews, confirmation with related figures and agencies, and documentation studies. The results indicate that Lhokseumawe City has great potential for the development of women's entrepreneurship and fostering the quality of entrepreneurship to be more resilient and independent. The inhibiting factors for entrepreneurship are the weak access to funding and the lack of awareness of the local government. The most important factor for entrepreneurial success was the spiritual spirit given by the family, especially their husbands, parents, and spiritual teachers. The involvement of the Lhokseumawe City government, sub-district government, village government, academics, banks, large companies in the tourism object environment, non-governmental institutions/NGOs, and the private sector MSMEs in Lhokseumawe can realize the success of halal tourism in Lhokseumawe. The Lhokseumawe City Government has fully supported Acehnese women's entrepreneurial activities.